The supernatural society - Ogle, Rex (Inkyard Press, 2022)
Will Hunter thought his life couldn't get any worse - his parents just got divorced ; his best (and only) friend now is his dog, Fitz ; and his Mom moved them from New York City to a middle-of-nowhere town called East Emerson. But Will was wrong - things are about to get way worse. Because East Emerson is filled with a whole lot of monsters that only he can see. To everyone else they look like normal people. When all the town pets (including Fritz), go missing, Will suspects there's something sinister going on. So he joins forces with outcast Ivy and super smart Linus to uncover the ancient secrets of East Emerson. Besides, nothing bad could happen when three sixth graders team up against a town full of monsters - right?--